Analisis Teknik Lompat Jauh Gaya Jongkok Pada Siswa Kelas V SD Negeri 19 Kota Bengkulu - Ritonga, Febriyanto; Sumantri, Ajis; Syaputra, Roni (Educative Sportive, 2024)
Long bounce may be a shape of development hopping, lifting the legs up forward in an exertion to carry the body's weight as long as conceivable within the discuss (floating within the air) which is done rapidly. body as long as conceivable within the discuss (drifting within the discuss) which is done rapidly and with a way to create a repugnance on one foot to reach the remove and by way of making a shock on one foot to attain the farthest separate as distant as conceivable. Components that influence the most extreme long hop incorporate leg length, leg muscle hazardousness, running speed when taking the prefix, shock or take off, body demeanor within the discuss and landing. In expansion, competitors must moreover have quality, hazardous control, speed, precision, adaptability, nimbleness and coordination of developments must too get it and ace the procedures to perform long bounce developments, and be able to do it rapidly, exact, adaptable and smooth. long bounce capacity of review V understudies of Rudimentary School State 19 Bengkulu City gotten the comes about of the long hop test with an normal of 81.25 and is within the great category or in this case competent.